Adentrando os espaços de aprendizagem da coordenação pedagógica: um estudo na perspectiva da psicogenética walloniana - Herculano, Silvia Cristina (2016)
This research has as aim to investigate learning spaces of the pedagogical coordinator, as well as to analyze the perception by the relations established in the different spaces of interaction in the school context. Pedagogical coordinator is the responsible professional for processes formation docent, he accompanies the student learning, he also interacts with the management team and with the students' family, him field of experience and learning has as aim of study in the ambit of initial and continuing formation and the researches for the formative processes of educators. The procedure of the information s collect had as grounding the qualitative methodological approach held through individual interviews with three pedagogical coordinators of municipal schools early childhood education of São Paulo, previously, they were selected from the following characteristics: pedagogical coordinator beginner in function, pedagogical coordinator with some years of experience and pedagogical coordinator finishing your career. The theoretical reference that subsidy the discussion is the wallonian psychogenetics, once the analysis of the resulting search of the narratives of pedagogical coordinators enable to enumerate three axes that link the conditions for learning of pedagogical coordinators: learning spaces experienced in professorship and in the pedagogy; learning spaces in docents activities and learning spaces at school that they act. The results indicate that pedagogical coordinator considers like learning spaces those who bring the condition of formation focused on pedagogical practice, the experiences as a teacher and contexts of interaction in the exercise of coordination function